Gender differences in the Israeli academia: a bibliometric analysis of different disciplines. Issue 2 (7th January 2021) - Cooper, Tzipi; Aharony, Noa; Bar-Ilan, Judit
Abstract : Purpose: This study explores faculty members' outputs and citations by gender and academic rank in Israeli academia. The study focuses on the connection between research productivity and underrepresentation of women in academia. To this end, four fields were chosen, each representing a different discipline: Psychology (social sciences), Public Health (health sciences), Linguistics (humanities), and Chemistry (Exact sciences). Design/methodology/approach: The name, the rank and the gender of the researchers were collected from the researchers' websites and those of their departments. The number of publications and citations were retrieved from Scopus. Findings: Findings revealed that there is a significant difference between the median number of men and women in Chemistry concerning publications and citations and in Psychology concerning citations. Moreover, in all four disciplines, females' average number of publications was lower than that of males', and that in three out of the four disciplines (Psychology, Public Health and Chemistry), men published more in top journals (the top 5%) than females, while the reverse was true of Linguistics. Furthermore, in three disciplines (Public Health, Linguistics and Chemistry), there is an increase in the average citations per female researchers between 2015 and 2019. Further, in all disciplines, women collaborated more than men. Originality/value: As only a few studies in Israel have explored faculty members' outputs and citations, this study contributes and enlarges the Israeli research concerning this topic.